Low cost incoherent pump solution for Raman fiber amplifier - Rocha, Ana M.; Neto, Berta; Facao, Margarida; Andre, Paulo S. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this work, we demonstrate the implementation of a low cost broadband pump source for Raman amplification. The advantages of this incoherent pumping scheme were demonstrated by compar-ing, experimentally and numerically, this solution with the one based on coherent pumping. We observed a decrease by 1.4 dB in the Raman gain ripple and a 16% increase in the bandwidth, for the latter solution.
Optica Applicata, Vol. 39, 2009, nr 2, s. 287-293
Keywords: optyka; Raman fiber amplifier; incoherent pump